ANALYSIS THE EFFECT OF GOOD CORPORATE GOVERNANCE ON CORPORATE VALUE WITH CORPORATE SOCIAL RESPONSIBILITY AS MODERATING VARIBLE - SYADZLI WARDANA (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
Indonesia has entered a new phase in economic development, It requires everyeconomic actor to realize the importance of maintaining commitment of development informations for deciding investment necessity. The necessity of information is not only seeing the condition of the economy but also the necessity of environmental and social informations as an important factor that influence a value of a company in Indonesia. This study aims to determine the effect of Good Corporate Governance that proxied by Institutional Ownership and the Proportion ofIndependent Board of Commissioners to the corporate value, while corporate value ismeasured using Tobins'Q, and whether Corporate Social Responsibility can moderate the influence of Good Corporate Governance to the corporate value. Theanalysis was performed using Multiple Linear Regression and Moderated Regression Analysis. The results of this study found that the Good Corporate Governance has apositive influence on corporate value and the disclosure of Corporate SocialResponsibility is able to moderate the influence of Good Corporate Governance oncorporate value. Keywords: Corporate Social Responsibility, Good Corporate Governance, Tobins’Q